Assata's (Groove[ing]) Daughter: An Embodied Lyrical Autoethnography of Resistance. Issue 2 (August 2021) - Hill, Dominique C.
This embodied lyrical autoethnography expands the look of freedom fighting. (Re)turning to a lasting mother–daughter lesson with new eyes and Assata Shakur's insistence that liberation is a duty, it introduces "groove[ing]" as a form of freedom fighting. Organized around and through three corresponding images taken at Stone Quarry Art Park, it renders visible quotidian and impactful movements made by a Blackgxrlwomxn when (re)membering lessons from childhood to incite pleasure amidst a pandemic.